An Inquiry into the Relationship Between Spiritual Intelligence and Sexual Perceptions of College Students - Ara R. Justol; Mel Lenosh M. Egar; Raunian Dave S. Bagbag; Winston Jan Philip D. Galarosa; Eljoy L. Linggay; Whilmar B. Porras; Evan P. Taja-on (Indonesian Journal of Christian Education and Theology, 2026)
The search for meaning through spirituality often guides how individuals view themselves and the world, shaping values and decisions in daily life. At the same time, sexual perceptions play an important role in personal identity, and their interaction with spirituality reveals both harmony and conflict in student experiences. The inquiry gathered responses from college students through a structured survey, ensuring representation from all academic departments, which summarized student views and identified meaningful connections between spirituality and sexuality. The findings show that college students with stronger reflective and meaning-oriented capacities tend to demonstrate higher awareness of sexual matters, particularly in areas related to identity and health. This connection highlights the role of inner awareness in shaping informed and respectful views on sexuality. These results suggest that fostering reflective awareness among college students may support healthier and more informed understandings of sexuality across diverse contexts.